Digitalization of Bale Kampoeng Radjoet SMEs Stock Opname Recording Systems based on Website with Waterfall Method - Fredicia Angelia Kezia Boanito Sirait; Endang Chumaidiyah; Tiara Verita Yastica (School of Industrial and System Engineering, Telkom University, 2023)
Bale Kampoeng Radjoet is an SME in Bandung that markets knitting products from 12 artisans. In thebusiness process, recording product data is still done manually using a notebook. This has an impact on thestock opname process, namely the occurrence of product data discrepancies in the warehouse with recordsand difficulties in knowing product stock. These problems are caused by the absence of a system that helpsrecord all product data. This is the basis for improving the stock opname recording system by digitalization,namely the use of a website-based information system. The development of the stock opname recordingwebsite uses the waterfall method, with system modeling using the Unified Modeling Language (UML). Thesystem verification process uses blackbox testing and validation using User Acceptance Testing (UAT)which refers to ISO 25010. UAT results show the characteristics of functional suitability 89.33%,performance 92%, usability 91.2%, and reliability 93.33%. The results adjusted to the interpretation criteriashow that the four characteristics are in the range of 81%-100%, which means that the website can beaccepted by users because it fulfills user needs and can be run according to its function